(untitled) (Journal of Atomic and Molecular Sciences, 2021)
In this article, we do a research on the chiral shift process of the isolated alpha alanine molecule using the basis set of 6-31+g(d,p), which is based on density functional theory B3LYP. Furthermore, the chiral transition path reaction potential energy surface of ibuprofen molecule is drawn by looking for the extreme value point structure including the transition state and intermediate. Finally, the geometry and electronic structure properties of extreme value point are also analyzed. The results show that there are two achieve reaction paths of ibuprofen from S-type to R-type. Path 1 consists of three transition states and two intermediate states. Path 2 includes four transition states and three intermediate states. On the reaction path, the greatest barrier which is from the transfer of hydrogen in chiral carbon to oxygen in carboxyl, is 73.54 Kcal/mol. The research provides a theoretical reference to further realize some important application value over the chiral transition reaction control of point chiral molecule.